Delirium in elderly patients: association with educational attainment. Issue 2 (9th August 2016) - Martins, Sónia; Paiva, José Artur; Simões, Mário R.; Fernandes, Lia
Abstract : Objective: Among cognitive reserve markers, educational attainment is the most widely studied, with several studies establishing a strong association with risk of dementia. However, it has not yet been fully examined in delirium. This study aims to analyse the relationship between educational attainment and delirium. Methods: The study included elderly hospitalised patients admitted (≥48 h) into an intermediate care unit (IMCU) of Intensive Care Medicine Service. Exclusion criteria were as follows: Glasgow Coma Scale (total≤11), blindness/deafness, inability to communicate or to speak Portuguese. The European Portuguese Version of the Confusion Assessment Method (CAM) was used for delirium assessment. Results: The final sample ( n =157) had a mean age of 78.8 (SD=7.6) the majority being female (52.2%), married (51.5%) and with low educational level (49%). According to CAM, 21% of the patients had delirium. The delirium group presented the fewest years of education (median 1 vs. 4), with statistical significance ( p =0.003). Delirium was more frequent among male patients [odds ratio (OR) 0.32; 95% confidence interval (CI) 0.12–0.86; p =0.023], as well as those patients with lower education (OR 0.76; 95% CI 0.62–0.95; p =0.016), and with respiratory disease (OR 3.35; 95% CI 1.20–9.33; p =0.020), after controlling for age and medication. Conclusion: Similar to previous studies, these findings point to a negative correlation between education and delirium. This study appears as an attempt to contribute to the knowledge about the role of cognitive reserve in risk of delirium, particularly because is the first one that has been carried out in an IMCU, with lower educated elderly patients. Further studies are needed to clarify this relationship considering other markers (e.g. cognitive activities), which can contribute to the definition of preventive strategies.